Tracing the spatiotemporal phylodynamics of Japanese encephalitis virus genotype I throughout Asia and the western Pacific. - Fan Li; Yun Feng; Guowei Wang; Weijia Zhang; Shihong Fu; Zuosu Wang; Qikai Yin; Kai Nie; Juying Yan; Xuan Deng; Ying He; Liang Liang; et al. (Public Library of Science (PLoS), 2023)
Background Japanese encephalitis virus (JEV; Flaviridae: Flavivirus) causes Japanese encephalitis (JE), which is the most important arboviral disease in Asia and the western Pacific. Among the five JEV genotypes (GI-V), GI has dominated traditional epidemic regions in the past 20 years. We investigated the transmission dynamics of JEV GI through genetic analyses. Methods We generated 18 JEV GI near full length sequences by using multiple sequencing approaches from mosquitoes collected in natural settings or from viral isolates obtained through cell culture. We performed phylogenetic and molecular clock analyses to reconstruct the evolutionary history by integrating our data with 113 publicly available JEV GI sequences. Results We identified two subtypes of JEV GI (GIa and GIb), with a rate of 5.94 × 10-4 substitutions per site per year (s/s/y). At present, GIa still circulates within a limited region, exhibited no significant growth, the newest strain was discovered in China (Yunnan) in 2017, whereas most JEV strains circulating belong to the GIb clade. During the past 30 years, two large GIb clades have triggered epidemics in eastern Asia: one epidemic occurred in 1992 [95% highest posterior density (HPD) = 1989-1995] and the causative strain circulates mainly in southern China (Yunnan, Shanghai, Guangdong, and Taiwan) (Clade 1); the other epidemic occurred in 1997 (95% HPD = 1994-1999) and the causative strain has increased in circulation in northern and southern China during the past 5 years (Clade 2). An emerging variant of Clade 2 contains two new amino acid markers (NS2a-151V, NS4b-20K) that emerged around 2005; this variant has demonstrated exponential growth in northern China. Conclusion JEV GI stain circulating in Asia have shifted during the past 30 years, spatiotemporal differences were observed among JEV GI subclade. GIa is still circulating within a limited range, exhibite no significant growth. Two large GIb clades have triggered epidemics in eastern Asia, all JEV sequences identified in northern China during the past 5 years were of the new emerging variant of G1b-clade 2.